Social and Linguistic Change in European French - Armstrong, N. author. aut Link
XVII, 310 p. 16 illus.
Keywords: An in depth examination of linguistic variation and change as a reflection of social convergence in the major French-speaking countries of Europe - France, Belgium and Switzerland. Considered in the context of linguistic levelling the book provides a detailed account of recent social and linguistic change in European French.